The Common Indian Ginseng - Bennet, S. S. R.; Viswanathan, M. V. (Indian Forester, 1984)
Field study of the Panax species in India revealed that Panax pseudoginseng var. angustifolius should be given specific rank as P. burkillianus; the study is based on leaflet and rbizome morphology. The species is the common Indian Ginseng.